ANALISIS ISI LAMBUNG IKAN TAPAH (Wallago leeri) DI PERAIRAN SUNGAI SIAK DAN SUNGAI KANDIS DESA KARYA INDAH KECAMATAN TAPUNG - Susi Kemala Sari; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A study on gut content analysis of Tapah fish (Wallago leeri) at two stations of Siak andKandis river has been carried out in February to July 2013. The objective of this study wasto know about the kinds of food for Tapah fish,such as main, suplement and additional foodin Siak and Kandis river. The data was analyzed using the Index of Preponderance (thelargest part index) by Natarjan and Jingran cit. Effendie (1979). The result of thestudyrevealed that the main food of Tapah fish in Siak river station consists ofCyclocheilichthyssp. (48%), the supplement food consists of Ompok sp. (28%), Puntius sp.(12%), and animal debris (11%), whereas additional food is Rasbora sp. (1%). Tapah fishin Kandis river has main food which consists of Cyclocheilichthys sp. (43%), and supplementfood consists of Ompok sp. (27%), Puntius sp. (10%), and animal debris (18%). As anadditional food, Tapah fish also feeds on Rasbora sp. (2%).